(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2021)
During the restoration process, the experts from JAICA, made a chance discovery of a mural. But unfortunately, its viewing was/is almost totally blocked by an extra wall, built right in-front of the actual wall, with the murals. To demystify the contents, it has had remained a professional challenge, as it could be barely viewed by one end only – from within a space between 8-9 inches gap. It posed challenge for many reasons. First was its difficult location. Secondly, the painted wall was also damaged beyond descriptions – plaster-surface peeled off spread all over – making the task to read the images even harder. Most importantly, to read the contents or to identify the imageries in such a location, it asked for a professional ability of an art writer or an art historian, to be able to read and analyze. However, after a very meticulous effort and a proper reading of the postures, emblems and other iconographical features, the narratives are being made – explaining on and about the murals found. The essay is prepared and is made, after a series of exercises – begun by field visits, and followed by closer examination of the images on the spot and as is available in digital images. The writing is made - after the long afterthoughts, and in consultation with the available references.